Positron Emission Tomography for Future Drug Development - Minamimoto, Ryogo; Theeraladanon, Chumpol; Suzuki, Akiko; Inoue, Tomio (Recent Patents on Medical Imaging (Discontinued), 2011)
Productivity in the drug discovery and development process has seen a drastic decline over the last few years. Clearly, traditional approaches to drug development are not working. The new concept called “microdosing studies” was recently announced as a promising methodology for accreting drug development. The microdosing studies is a concept by administrating a low dose (microdose) of a candidate compound to human volunteers to obtain in vivo human pharmacokinetic (PK) data at an early stage of drug development. As a result unpromising candidate drugs can be eliminated at an earlier stage of drug development. A key component for this concept is highly sensitive analytical methods such as positron emission tomography (PET), accelerator mass spectrometry (AMS) and liquid chromatography-mass spectrometry (LC/MS/MS). This issue focuses on PET methodology from basic to future prospects for drug development and patents related to it.
Keywords: radiopharmaceutical sciences